Peningkatan SDM di Pulau Harapan melalui Pelatihan Pengelolaan Standar Usaha Homestay dalam Mendukung Program Visit Pulau Seribu 2023 - Taufik Hidayat; Adriyanto, Hendaris; Arisandi, Bustomi (LPPPM STAI Darul Hikmah Bangkalan, 2024)
Harapan Island, located in the Thousand Islands, holds amazing natural beauty, where the view of the sea, white beach sand, coral reefs, and beautiful island scenery are the main attractions. The people of the Thousand Islands, in addition to living from marine products or fishermen, have also started to develop the economy through tourism activities, this is marked by the beginning of many people who have changed the function of their houses into homestays to tourists. To develop Homestay accommodation that has excellent service standards, it is not easy for the people in the Harapan Islands considering that the number of human resources who have competence in this field is still limited. For the community, there must be a change in attitude in maintaining the status of Homestay, such as preserving the village environment, maintaining cleanliness, maintaining cultural and spiritual sustainability, fostering creativity and innovation to grow and manage the resources owned, and most importantly, to increase knowledge and understanding related to tourism. This activity uses the Asset Based Community Development method, which is training for Pokdarwis in the form of a socialization program for Homestay business standards which aims to provide understanding to Homestay owners on Harapan Island. The results of this training are expected to improve the competence and capabilities of human resources to welcome tourists through the